Peran Pemasaran Digital dalam Meningkatkan Daya Saing Produk Olahan Mangga di Desa Jembarwangi, Sumedang Jawa Barat - Sikki, Nurhaeni; Ratna Deli Sari; Rachmawati, Eva; Rahayu, Hanny; Gunawan, Yanyan; Aisyah, Sitti Nur; Rachmansyah, Farhan (Jurnal Pengabdian Kepada Masyarakat, 2025)
Jembar Wangi Village, located in Tomo District, Sumedang Regency, West Java, holds significant potential as a center for gedong gincu mango production. However, a large volume of rejected mangoes that do not meet market standards leads to environmental problems due to fruit spoilage. This study aims to identify solutions for processing rejected mangoes through community empowerment based on micro-enterprises. The methods employed include community service by university students (KKN) and training programs funded by the 2024 DRTPM PKM Grant and the 2025 Competitive Grant from Sangga Buana University. The training covered mango chip production, packaging, business administration, and marketing. The results indicate an increase in production capacity through the provision of equipment such as vacuum fryers, slicing machines, and storage facilities. Furthermore, active participation of local women’s groups in the production process increased significantly. The discussion focuses on community empowerment—particularly among women farmers—and the challenges in marketing, which still rely on conventional methods. Product development strategies involving digital marketing (e-commerce and village websites) and trademark registration show potential to expand market reach and strengthen local product identity. This program has had a positive impact on women's economic empowerment and has contributed to sustainable community welfare. The findings can serve as a replicable model for local economic empowerment in other.